Experimental model of obtaining tissue adipose, mesenchymal stem cells isolation and distribution in surgery flaps in rats - Freitas,André Luiz Pires de (2014)
PURPOSE:To investigate the experimental model for obtaining adipose tissue, isolation, characterization of mesenchymal stem cells and evaluation of their distribution in the tram flap in rats.METHODS:Five rats of Wistar were randomly assigned to two groups. In group I, three animals underwent removal of adipose tissue in the groin procedure to establish the experimental model and obtain a cell lineage. The animals of group II (n = 2) underwent surgical flap procedure, and satisfaction injection of mesenchymal stem cells pretreated with marker fluorescente.RESULTS:obtaining adipose tissue of the inguinal region of the rat proved to be possible. The isolated cells were characterized as mesenchymal stem cells and fluorescence microscopy showed the presence of multiple cells arranged around blood vessels and capillaries.CONCLUSION:It was possible to establish an experimental model for obtaining adipose tissue for isolation of mesenchymal stem cells and their distribution in the TRAM flap in rats.